How Participatory is Participatory Irrigation Management - Souvik Ghosh , P. S. Brahmanand , K. G. Mandal , P. Nanda; D. U. Patil (Indian Journal of Extension Education, 2016)
An assessment of Participatory Irrigation Management (PIM) was carried out in Kuanria Medium Irrigation Project in Nayagarh district of Odisha covering 10 WUAs with a sample survey of 350 farmers. Methodologies developed to assess farmers’ perceptions towards extent of participation, utility of irrigation service and performance of water user association (WUA) in the command area (varied from 274.95 ha to 501.70 ha) under the WUAs. Overall participation of the farmers was below average in case of all the 10 WUAs as evident from lower farmers’ participation index values (<50%). The irrigation performance found better in kharif season as compared to rabi season in most of the WUA’s jurisdiction areas. WUA’s performance perceived below average and varied over the space. Analyses of agricultural performances in the WUAs jurisdiction command area revealed that WUAs at tail reach recorded cultivated land utilisation index lower than 50%; the crop diversity index and multiple cropping index were found low as the farmers didn’t cultivate any crop during rabi season due to paucity of irrigation water at tail end.